Navigating Generosity: Exploring Determinants of Zakat, Infaq, and Sadaqah among the Hijrah Community in the COVID-19 Pandemic - Azhar, Neng Zulfa; Nofrianto, Nofrianto; Khan, Abdul Karim; Chantarungsri, Chariyada (Universitas Muhammadiyah Surakarta, 2024)
This study investigates the factors influencing the hijrah community's decision to contribute to Zakat, Infaq, and Sadaqah (ZIS) during the COVID-19 pandemic in Indonesia. Drawing upon the Theory of Planned Behavior (TPB), we examine the impact of religiosity, altruism, subjective norms, behavioral control, and institutional image on ZIS payment decisions. Data were collected through a questionnaire survey of 255 members of the hijrah community and analyzed using ordinal logistic regression. Results indicate that religiosity, altruism, and subjective norms significantly influence the decision to pay ZIS, while behavioral control and institutional image do not. This suggests that individuals with strong religious convictions, driven by empathy and a sense of social responsibility, and influenced by their social networks, are more likely to contribute to ZIS, regardless of perceived ease or institutional factors. This preference for direct giving, motivated by trust and a desire for tangible impact, further explains the limited influence of institutional image. This study contributes to the understanding of ZIS giving behavior within the increasingly prominent hijrah community, particularly during times of crisis, and offers valuable insights for Islamic philanthropic institutions seeking to maximize ZIS collection by tailoring their strategies to align with the motivations and values of this growing segment of donors. While this study focuses specifically on the hijrah community in Indonesia, future research should explore these factors among diverse Muslim populations in various socio-cultural contexts to enhance the generalizability of the findings.